2011
DOI: 10.5005/jp-journals-10024-1077
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Electron Microscopic Study of Surface Epithelial Cells in Erosive and Nonerosive Oral Lichen Planus

Abstract: Aim: Aim of the study is to study the surface epithelial cells of erosive, nonerosive lichen planus by scanning electron microscope (SEM) and to correlate it with that of normal mucosa and oral leukoplakia. Materials and methods:Twenty biopsies of lichen planus and five biopsies of normal mucosa were taken. Half piece of each biopsy was processed for H&E stain and another half for SEM study. Result: Surface epithelial cells were showing different features. Conclusion:Definite different features were seen in li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…Tracking the development of the palate, we found that the epithelial cells shifted from an irregular shape and malalignment without a clear border to a regular and orderly alignment with a clear border, showing that the surface layer cells changed and matured with the development of the epithelium. When the palate form took clear shape at E50, the epithelial cells under SEM were similar to those of the mature hard palate, with ridges surrounding uniform pits or a honeycomb pattern of interconnecting ridges surrounding depressions (Philipsen et al, ; Grossman,; Worawongvasu, ; Thakur and Hazare, ; Asikainen et al, ). Under TEM, we found that when the palate developed rapidly from E26 to E35, both epithelial and mesenchymal cells were not very differentiated and had huge nuclear regions with a large nucleus rich in euchromatin and nucleoli, with many depressions on the nuclear envelope surface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tracking the development of the palate, we found that the epithelial cells shifted from an irregular shape and malalignment without a clear border to a regular and orderly alignment with a clear border, showing that the surface layer cells changed and matured with the development of the epithelium. When the palate form took clear shape at E50, the epithelial cells under SEM were similar to those of the mature hard palate, with ridges surrounding uniform pits or a honeycomb pattern of interconnecting ridges surrounding depressions (Philipsen et al, ; Grossman,; Worawongvasu, ; Thakur and Hazare, ; Asikainen et al, ). Under TEM, we found that when the palate developed rapidly from E26 to E35, both epithelial and mesenchymal cells were not very differentiated and had huge nuclear regions with a large nucleus rich in euchromatin and nucleoli, with many depressions on the nuclear envelope surface.…”
Section: Discussionmentioning
confidence: 99%
“…Most descriptions of the ultrastructures of the oral mucosa involve comparison of normal oral epithelium and pathologic changes such as inflammation and cancer. In these reports, the orthokeratinized mucosa (hard palate) is described under SEM as having ridges surrounding uniform pits or a honeycomb pattern of interconnecting ridges surrounding depressions (McMillan, ; Philipsen et al, ; Grossman, ; Worawongvasu, ; Thakur and Hazare, ; Asikainen et al, ). Palate mucosa from 7 to 22 weeks in human embryos, 18 days of gestation in mice, and 1, 3, 7, 14, 21, 30, and 90 days after birth of human have been investigated by SEM and TEM, but the information is not detailed and systematic.…”
Section: Discussionmentioning
confidence: 99%
“…It has been documented that nano-architectural changes of the epithelial surface evaluated with scanning electron microscopy (SEM) can indicate the malignant potentiality of OPMD (Yoshimura et al, 2005; Asikainen et al, 2017). Variation in cell surface attributes like smoothness and pattern of microridges have been studied qualitatively by SEM in leukoplakia, lichen planus, and OC (Thakur & Hazare, 2011; Bánóczy, 2012). In the case of OSF, Bag et al (2015) have shown that there is a relationship between changes in molecular expressions and epithelial surface micro/nano alterations.…”
Section: Introductionmentioning
confidence: 99%